2009
DOI: 10.1111/j.1365-2621.2009.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of irradiation to extend the shelf‐life of clams (Ruditapes decussatus) during live storage: effect on bacterial and biochemical profiles

Abstract: Changes in microbiological and biochemical quality of clams (Ruditapes decussatus) subjected to low doses of gamma irradiation (0.5 and 1 kGy) were investigated during alive storage, at 5°C. The mortality rate was significantly lower for irradiated clams compared with the control. In the same way, ammonia content was lower for irradiated clams (especially 1 kGy irradiated group). Considerable levels of total mesophiles, coliforms, staphylococcus, faecal streptococcus and Escherichia coli were detected in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Irradiation as the only known method to pasteurize live molluscs without significantly aff ecting mortality (Mbarki et al, 2009). In our study, the survivability of control group was 19.7+0.6 of 20 oysters (98.5%) after storage of oysters at 5°C for 20 days (Table 1).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…Irradiation as the only known method to pasteurize live molluscs without significantly aff ecting mortality (Mbarki et al, 2009). In our study, the survivability of control group was 19.7+0.6 of 20 oysters (98.5%) after storage of oysters at 5°C for 20 days (Table 1).…”
Section: Resultsmentioning
confidence: 58%
“…Lopez-Caballero et al, (2000) stated bacteria would be the reason of high total volatile base (TVB) and small amounts TMAO (Trimethylamine N-oxide) during oyster spoilage because it produces amines, ammonia and reduced the pH by proteolytic and saccharolytic process. Through improving the microbial quality might alleviate biochemical changes during refrigerated storage (Mbarki et al, 2009). Buzin et al (2011) reported cold storage of Pacific oyster (Crassostrea gigas) remained a low mortality rate and the sensory attributes, odor, appearance, texture and flavor, did not show significant variations.…”
Section: Resultsmentioning
confidence: 99%
“…Yin et al (2014) reported that the lipid oxidation in grass carp fillets reduced the sensory parameters, including morphology, odor, color and muscle elasticity during frozen storage. Mbarki et al (2009) also stated that the polyunsaturated fatty acids underwent more oxidative changes than the saturated fatty acids, which was affirmed by an increase in saturated fatty acids and a decline in polyunsaturated fatty acids during frozen storage. Estevez et al (2005) examined that fat content is a key component, which may play a key role in lipid and protein oxidation during frozen storage of aquatic foods.…”
Section: Lipid Oxidationmentioning
confidence: 95%
“…Mbarki et al. (2009) also stated that the polyunsaturated fatty acids underwent more oxidative changes than the saturated fatty acids, which was affirmed by an increase in saturated fatty acids and a decline in polyunsaturated fatty acids during frozen storage. Estevez et al.…”
Section: Freeze‐induced Changes Of Aquatic Foodsmentioning
confidence: 96%
“…This result gives an opportunity to use radiation treatment as a means of improving the color in various food products in industrial application . Mbarki et al (2008Mbarki et al ( , 2009) reported elimination of mesophilic and psychrophilic germs of Bonito (Sarda sarda) at a dose of ≥1.5 kGy. Irradiation with doses of 6 and 7.5 kGy resulted in a decrease of polyunsaturated fatty acids which is an indication of enhancing the rate of lipid oxidation.…”
Section: Microbiological Safety and Nutritional Adequacymentioning
confidence: 98%